2018
DOI: 10.1111/jon.12591
|View full text |Cite
|
Sign up to set email alerts
|

Gray vs. White Matter Segmentation of the Conus Medullaris: Reliability and Variability in Healthy Volunteers

Abstract: BACKGROUND AND PURPOSE Magnetic resonance imaging (MRI)‐derived spinal cord (SC) gray and white matter (GM/WM) volume are useful indirect measures of atrophy and neurodegeneration over time, typically obtained in the upper SC. Neuropathological evidence suggests that in certain neurological conditions, early degeneration may occur as low as the sacral SC. In this study, the feasibility of GM/WM segmentation of the conus medullaris (CM) was assessed in vivo. METHODS Twenty‐three healthy volunteers (11 female, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 22 publications
2
18
3
Order By: Relevance
“…5 We also show for the first time that the measurement of the spinal canal area performed on spinal cord scans can significantly reduce inter-subject variability of SC areas, particularly when accounting for sex (TCA %RSD reduction by 15.52%, 12.15% for GMA). This finding is in contrast to a recent study performed at the lumbar level of the SC that showed no improvement of TCA inter-subject variability after normalization by spinal canal area, 39 which might be explained by the higher inter-subject variability of cord and spinal canal anatomy at the lumbar compared to the cervical level. Normalizing for head size using the SienaX-derived V-scale also reduced inter-subject variability, but to a lesser extent (10.24% for TCA, 8.28% for GMA).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…5 We also show for the first time that the measurement of the spinal canal area performed on spinal cord scans can significantly reduce inter-subject variability of SC areas, particularly when accounting for sex (TCA %RSD reduction by 15.52%, 12.15% for GMA). This finding is in contrast to a recent study performed at the lumbar level of the SC that showed no improvement of TCA inter-subject variability after normalization by spinal canal area, 39 which might be explained by the higher inter-subject variability of cord and spinal canal anatomy at the lumbar compared to the cervical level. Normalizing for head size using the SienaX-derived V-scale also reduced inter-subject variability, but to a lesser extent (10.24% for TCA, 8.28% for GMA).…”
Section: Discussioncontrasting
confidence: 99%
“…The variables non-significantly contributing to a model in an exploratory analysis were excluded, and the effect of the normalization by a particular selected model was evaluated by comparing the relative standard deviations (ratios of the group standard deviation and the respective means, %RSD) between the measured data and the values generated by the respective correction formulas. 38,39 Sample size calculations-To inform the design of research protocols for clinical trials using spinal cord areas as an outcome measure, we performed sample size calculations for two distinct clinical trial scenarios. Sample size calculations (with 90% power at 0.05 statistical significance) were made for the raw cord area values and for the values normalized with the best model, using a two-sided test.…”
Section: Comparison Of Different Normalization Methods-multiple Regression Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preganglionic neurons of the IML column of the sacral spinal cord are responsible for the innervation of the detrusor [25] and involvement of this region is likely to be responsible for detrusor failure. Routine MRI sequences of the lower cord are insensitive to identify degenerative changes in the lumbosacral spinal cord; however, high-resolution MR imaging protocols have successfully imaged the lumbosacral enlargement [26] and conus medullaris [27] and changes of grey matter atrophy have been demonstrated in MSA [28].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the normalization by a particular selected model was evaluated by comparing the coefficient of variation (%COV, ratio of the group standard deviation and the respective means expressed as percentage) between the measured data and the values generated by the respective correction formulas 10,15,16 …”
Section: Methodsmentioning
confidence: 99%